Changes in fat uptake, color, texture, and sensory properties of Aloe vera gel‐coated eggplant rings during deep‐fat frying process. Issue 4 (27th January 2023) - Varidi, Mehdi; Ahmadzadeh‐Hashemi, Saba; Nooshkam, Majid
Abstract: There is a widespread use of deep‐fat frying in both domestic and industrial sections, and deep‐fat fried foods are extremely popular due to their taste, color, and crispy texture. Human health can be, however, seriously compromised by the excessive consumption of oil, especially saturated fats and trans fatty acids. The use of hydrocolloids in inhibiting oil absorption has garnered considerable attention. This study was therefore aimed to lower the oil absorption in eggplant rings during the deep‐fat frying process with the aid of Aloe vera gel coating. The effects of gel concentration (0%, 50%, and 100%), frying time (2, 5, and 8 min), and frying temperature (160°C and 180°C) on the oil uptake, moisture content, texture, color, and sensory properties of the eggplant rings were evaluated. The gel coating led to a decrease in oil uptake (up to 50%), hardness (up to 0.98‐fold), Δ E (up to 0.89‐fold), and overall acceptance (up to 0.85‐fold), and an increase in moisture content (up to 1.47‐fold) and lightness (up to 1.14‐fold) of the samples. The frying time and temperature also influenced the physiochemical and sensory properties of the eggplant rings. The sample coated with 50% gel and fried at 180°C for 8 min had lower oil content and water loss with the highest acceptance rate in terms of taste, color, odor, texture, and appearance. The Aloe vera gel could be, therefore, a good candidate with high nutritional and economic value to reduce oil uptake in fried food products. Abstract : The sample coated with 50% gel and fried at 180°C for 8 min had lower oil content and water loss with the highest acceptance rate in terms of taste, color, odor, texture, and appearance. The Aloe vera gel could be a good candidate with high nutritional and economic value to reduce oil uptake in fried food products.